2020
DOI: 10.1136/annrheumdis-2020-219174
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory therapy for COVID-19 infection: the case for colchicine

Abstract: The search for effective COVID-19 management strategies continues to evolve. Current understanding of SARS-CoV-2 mechanisms suggests a central role for exaggerated activation of the innate immune system as an important contributor to COVID-19 adverse outcomes. The actions of colchicine, one of the oldest anti-inflammatory therapeutics, target multiple mechanisms associated with COVID-19 excessive inflammation. While many COVID-19 trials have sought to manipulate SARS-CoV-2 or dampen the inflammatory response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 70 publications
1
123
0
17
Order By: Relevance
“…Results such as these suggest, in light of the IRAP model presented here, that the most effective treatments for cytokine storms, whether in COVID-19 or other cytokine release syndromes, are most likely to be those that target either the key TLR-NLR synergistic sets that trigger a particular syndrome through broadly acting inhibitors such as melatonin or, perhaps, colchicine (which has a similar TLR antagonism profile [262][263][264][265][266]) or by means of TLR and/or antagonist combinations, thereby downregulating all cytokine production. It does not appear that either of these approaches has been systematically investigated in COVID-19, ALI-ARDS or sepsis, and even the use of melatonin in COVID-19 was initiated in apparent ignorance of its multiple TLR/NLR-moderating effects.…”
Section: Implications Of Innate Receptor Activation Profiles For Tretmentioning
confidence: 80%
“…Results such as these suggest, in light of the IRAP model presented here, that the most effective treatments for cytokine storms, whether in COVID-19 or other cytokine release syndromes, are most likely to be those that target either the key TLR-NLR synergistic sets that trigger a particular syndrome through broadly acting inhibitors such as melatonin or, perhaps, colchicine (which has a similar TLR antagonism profile [262][263][264][265][266]) or by means of TLR and/or antagonist combinations, thereby downregulating all cytokine production. It does not appear that either of these approaches has been systematically investigated in COVID-19, ALI-ARDS or sepsis, and even the use of melatonin in COVID-19 was initiated in apparent ignorance of its multiple TLR/NLR-moderating effects.…”
Section: Implications Of Innate Receptor Activation Profiles For Tretmentioning
confidence: 80%
“…Several studies have evaluated the benefit of colchicine in patients with COVID-19. A retrospective study of ICU patients with COVID-19 demonstrated a lower risk of death in patients on colchicine therapy [49]. The GRECO-19 study is demonstrated a significant reduction in the primary clinical outcome of a two-point deterioration on the WHO disease severity scale [50].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…4), that are now recommended for use in extreme cases of CoVID-19, is the goal of reducing extreme inflammation and ensuing elevated immune response that can be a key cause of CoVID-19 morbidity. 254 Although there have been debates about the general utility of corticoid steroids as therapies for CoVID-19, 255 dexamethasone at the time of writing, the only treatment approved to lower mortality of CoVID-19. 256 Treatments of over 10 days are considered only for the worst cases.…”
Section: Targeting Transcription: Remdesivirmentioning
confidence: 99%
“…290 Nevertheless, IL-6 inhibitors are being trialed; several of these also may have inherent antiviral activity. 291 Several other treatments have been proposed to suppress the principal symptoms of the disease, such as aspirin (shown to have little clinical effect in a study of 183 patients in China, 292 although pre-existing asprin prescription was found to decrease mortality), 293 tocizumab, 294 an immunosuppressive, and colchicine, an anti-inflammatory molecule used to treat gout 254 (initial patient data indicate a positive response in mild to severe CoVID-19 cases). 295 Oxidative stress is an important contributing factor to serious CoVID-19 cases and there are reports that CoVID-19 infection may suppress cellular antioxidant response.…”
Section: Targeting Infection and Harnessing Fortuitous Antiviral Effementioning
confidence: 99%